The Altitude of Coffee Cultivation Causes Shifts in the Microbial Community Assembly and Biochemical Compounds in Natural Induced Anaerobic Fermentations - Martinez, Silvia Juliana; Simão, João Batista Pavesi; Pylro, Victor Satler; Schwan, Rosane Freitas (Frontiers in Microbiology, 2021)
Coffee production above 1,000 m of altitude in the Caparaó region, MG, Brazil, is associated with high-quality beverages. We characterize, microbiologically and chemically, fermented coffees from different altitudes through target NGS sequencing, chromatography, and conventional chemical assays. The genera Gluconobacter and Weissella were dominant in coffee's fruits from altitudes 800 and 1,000 m. Among the Eukaryotic community, yeasts were the most dominant in all altitudes. The most dominant fungal genus was Cystofilobasidium, which inhabits cold environments and resists low temperatures. The content of acetic acid was higher at altitudes 1,200 and 1,400 m. Lactic acid and the genus Leuconostoc (Pearson: 0.93) were positively correlated. The relative concentration of volatile alcohols was high, especially of 2-heptanol in all elevations. Bacteria population was higher in coffees from 800 m, while at 1,000 m, fungi richness was favored. The altitude is an important variable driving the microbial community structure and content of biochemical compounds, even in coffees belonging to the same variety and cultivated in the same region under SIAF conditions.